In vivo efficacy of 2% povidone iodine, chlorhexidine gluconate, and herbal extract mouthwash on SARS-CoV-2 viral load in saliva: A randomized clinical trial - Sayana Nazrine; Ritesh Kulal; M B Shivaprasad; Nimmi Janardhanan (Wolters Kluwer Medknow Publications, 2023)
Background: One of the major techniques to reduce the transmission rate of COVID-19 would be to decrease the viral titers of SARS-CoV-2 in the saliva of infected patients and it is particularly useful in a dental setting. The present study evaluated the change in salivary viral load of COVID-19 patients using povidone iodine (PI), chlorhexidine (CHX), and an herbal extract (RightSure®) oral antiviral herbal mouthwash (HM) at clinically recommended duration and concentrations. Materials and Methods: Thirty individuals with SARS-CoV-2 were randomly allocated to three groups: (1) Group 1, PI mouthwash; (2) Group 2, CHX mouthwash; and (3) Group 3, HM mouthwash. A baseline salivary throat sample was collected from all the participants who were later instructed to rinse with their respective mouthwash for 30 s. A second salivary sample was collected 30 min after rinsing. The SARS-CoV-2 viral load was analyzed using real-time reverse-transcription polymerase chain reaction wherein the cyclic threshold (Ct) values were evaluated. Results: Independent t-test analysis reported a statistically significant difference concerning the PI group (before-after comparison) (P < 0.05). The rest of the two study groups failed to report any significant difference in the nucleocapsid gene and open reading frame 1a gene levels. Conclusion: While all three types of mouthwash increased the Ct values, a statistically significant difference was observed with PI mouthwash, indicating that it might potentially reduce the spread of the SARS-CoV-2 virus, especially via aerosol but further studies with larger sample size and longer follow-up periods are required to investigate this relationship.